2015
DOI: 10.1177/0734282915595303
|View full text |Cite
|
Sign up to set email alerts
|

Top Ten Standardized Tests Used Internationally With Children and Youth by School Psychologists in 64 Countries

Abstract: This article provides a 24-year update on the 10 standardized tests used most frequently with children and youth by school psychologists. Data were acquired from 64 countries through an international survey, with one respondent from each country. The informants were solicited due to their expertise in the area of assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 19 publications
(21 reference statements)
0
19
0
17
Order By: Relevance
“…The Wechsler Intelligence Scale for Children – Fifth Edition (WISC‐V; Wechsler, ) is the latest edition of one of the most popular intelligence tests in applied psychological practice and likely to be extensively used throughout the world (Oakland, Douglas, & Kane, ). Based on neuropsychological research and Cattell–Horn–Carroll (CHC) theory (CHC; Schneider & McGrew, ), which is an amalgam of the work of Carroll, Cattell, and Horn (Carroll, ; Horn, ; Horn & Cattell, ), two Wechsler Intelligence Scale for Children – Fourth Edition (WISC‐IV; Wechsler, ) subtests were deleted and three new subtests were added.…”
Section: Introductionmentioning
confidence: 99%
“…The Wechsler Intelligence Scale for Children – Fifth Edition (WISC‐V; Wechsler, ) is the latest edition of one of the most popular intelligence tests in applied psychological practice and likely to be extensively used throughout the world (Oakland, Douglas, & Kane, ). Based on neuropsychological research and Cattell–Horn–Carroll (CHC) theory (CHC; Schneider & McGrew, ), which is an amalgam of the work of Carroll, Cattell, and Horn (Carroll, ; Horn, ; Horn & Cattell, ), two Wechsler Intelligence Scale for Children – Fourth Edition (WISC‐IV; Wechsler, ) subtests were deleted and three new subtests were added.…”
Section: Introductionmentioning
confidence: 99%
“…The Wechsler instruments are commonly used measures of academic and cognitive functioning (Oakland et al, 2016) that have demonstrated generally high validity and reliability. A norm-referenced measure of intellectual ability, the WISC-IV CDN (Wechsler, 2003), provides an FSIQ comprising 10 primary subtests and four indices.…”
Section: Methodsmentioning
confidence: 99%
“…Verbal ability was assessed in each study via either a Stanford-Binet or Weschler intelligence test (or revisions thereof). These measures of verbal ability remain two of the top-ten most utilized psychometric tests in school systems around the world today (Oakland, Douglas, & Kane, 2016).…”
Section: Motivating Datamentioning
confidence: 99%